Increased IL-17A expression in temporal artery lesions is a predictor of sustained response to glucocorticoid treatment in patients with giant-cell arteritis. Issue 9 (19th September 2012) - Espígol-Frigolé, Georgina; Corbera-Bellalta, Marc; Planas-Rigol, Ester; Lozano, Ester; Segarra, Marta; García-Martínez, Ana; Prieto-González, Sergio; Hernández-Rodríguez, José; Grau, Josep M; Rahman, Mahboob U; Cid, Maria C
Abstract : Background: Interleukin 17A (IL-17A) exerts pivotal proinflammatory functions in chronic inflammatory and autoimmune diseases. Objective: To investigate IL-17A expression in temporal artery lesions from patients with giant-cell arteritis (GCA), and its relationship with disease outcome. Methods: Fifty-seven patients with biopsy-proven GCA were prospectively evaluated, treated and followed for 4.5 years (52–464 weeks). Relapses, time (weeks) required to achieve a maintenance prednisone dose <10 mg/day, and time (weeks) to complete prednisone withdrawal were prospectively recorded. IL-17A mRNA was measured by real-time quantitative RT-PCR in temporal arteries from all patients and 19 controls. IL-17 protein expression was assessed by immunohistochemistry/immunofluorescence. Results: IL-17A expression was significantly increased in temporal artery samples from GCA patients compared with controls (6.22±8.61 vs 2.50±3.9 relative units, p=0.016). Surprisingly, patients with strong IL-17A expression tended to experience less relapses, and required significantly shorter treatment periods (median 25 vs 44 weeks to achieve <10 mg prednisone/day, p=0.0079). There was no correlation between IL-17A and RORc or RORα expression suggesting that these transcription factors may not exclusively reflect Th17 differentiation, and that cells other than Th17 cells might contribute to IL-17 expression in active patients. Accordingly, FoxP3 + IL-17A + cells were identified in lesions by confocal microscopy and were dramatically reduced in specimens from treated patients. Conclusions: IL-17A expression is increased in GCA lesions, and is a predictor of response to glucocorticoid treatment. The contribution of FoxP3+ cells to IL-17A production in untreated patients suggests that induced-Tregs may facilitate disease remission when proinflammatory cytokine production is downregulated by glucocorticosteroids.